Effectiveness of therapeutic massage for improving motor symptoms in Parkinson's disease: A systematic review and meta-analysis - Kang, Zhiran; Xing, Hua; Lin, Qiang; Meng, Fanchao; Gong, Li (Frontiers in Neurology, 2022)
Background Parkinson's disease (PD) causes movement disorders [called motor symptoms (MS)], and motor dysfunction poses a great barrier to the quality of life. Although pharmacological therapy like levodopa can relieve the symptoms, it can also cause complications, such as psychosis, nausea, and dyskinesia. A therapy with more minor side effects is needed for PD. Therapeutic massages are the most commonly used forms of complementary and alternative medicine (CAM), but no systematic review and meta-analysis have focused on the efficacy of massage on PD. Objective To evaluate the quality of evidence and efficacy of therapeutic massage for improving MS in PD. Methods We independently searched four electronic databases, including Chinese National Knowledge Infrastructure (CNKI), MEDLINE/PubMed, Embase, and Cochrane Library, for randomized controlled trials (RCTs) about therapeutic massage and other available manual therapies improving MS in PD from January 1, 2012, to December 31, 2021 (recent 10 years). The main outcome measures were total effectiveness and the Unified Parkinson's Disease Rating Scale (UPDRS), including UPDRS total, II, and III. For the statistical analysis, the risk ratio, standard mean difference, and 95% confidence interval (CI) were used to calculate effect sizes between groups. To determine heterogeneity, statistical index I2 was used. Results A total of 363 PD participants in seven RCTs and one randomized pilot-control study were included in this meta-analysis. The total effectiveness showed that therapeutic massage was more effective than the intervention of the control group for improving MS [ratio risk (RR): 1.33, 95% CI (1.14–1.55), p = 0.0002]. The UPDRS-III scores showed that massage improves motor function more than the control group [SMD = −0.46, 95% CI (−0.67, −0.24), p < 0.00001]. But we found that massage performed no better than the control group in improving daily life activities [SMD = −0.15, 95% CI (−0.40, 0.10), p = 0.23]. Conclusion Therapeutic massage was effective in improving MS in PD. It is suggested to be an appropriate form of CAM in treating PD. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=323182, identifier: CRD42022323182.